Governos geisel e dilma: O poder das finanças - Angelita Matos, A. M. [UNESP] (Universidad Nacional de Colombia, 2015)
The goal is to identify the origin of the political power of finance in the final two governments of the military dictatorship, especially the Geisel government (1974-1978), understood as definitive in the political and economic history of Brazil in recent decades. We will also highlight similarities between the Geisel and PT governments; that they both adopt policies that are favorable for the productive sector, without opposing bank interests, despite the short time in which the Dilma government tried to lower bank interest.
Geisel and dilma governments: The power of finance
Keywords: Geisel government; Political hegemony; PT governments; State autonomy